2020
DOI: 10.1186/s12883-020-01839-5
|View full text |Cite
|
Sign up to set email alerts
|

Failure of preventive treatments in migraine: an observational retrospective study in a tertiary headache center

Abstract: Background: Although the criteria for acute migraine treatment and prevention have been well described, there are still unmet needs, general underuse and low benefits of preventive drugs. The aim of the present study was to retrospectively observe the short-term effect of preventive treatment in a cohort of migraine patients attending a tertiary headache center, using data from electronic medical records. Methods: This was an observational retrospective cohort study based on data collected in a tertiary headac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…In regard to the migraine cohort evaluated after 3 months preventive treatment, it is not a primary aim of the study to give comments about the effect of therapies. Briefly, present study confirmed what recently reported by our group, a high percentage of patients below the threshold of 50% headache frequency reduction, though in the present evaluation we found more responders [ 12 ]. There was also a general mild improvement of main migraine clinical aspects, while flunarizine confirmed a better effect on frequency and amitriptyline on mood.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In regard to the migraine cohort evaluated after 3 months preventive treatment, it is not a primary aim of the study to give comments about the effect of therapies. Briefly, present study confirmed what recently reported by our group, a high percentage of patients below the threshold of 50% headache frequency reduction, though in the present evaluation we found more responders [ 12 ]. There was also a general mild improvement of main migraine clinical aspects, while flunarizine confirmed a better effect on frequency and amitriptyline on mood.…”
Section: Discussionsupporting
confidence: 93%
“…They were visited after 3 months follow up. Some of the patients were also included in the previous evaluation, and we followed the same therapeutic options detailed in Delussi and de Tommaso [ 12 ]. Patients were considered responders if they reported a 50% reduction of headache frequency at follow up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct therapeutic approach to single causes of comorbidity in such complicated patients could improve their global clinical picture (Affaitati et al, 2020 ). A recent observational study on the effects of preventive treatments after 3 months of therapy showed that patients with FM have a profile of resistance to first-line preventive drugs (Delussi et al, 2020 ). Tricyclic antidepressant amitriptyline was actually the most frequently prescribed drug for the treatment of migraine patients comorbid with FM (Delussi et al, 2020 ).…”
Section: Comorbidity With Other Pain Syndromesmentioning
confidence: 99%
“…A recent observational study on the effects of preventive treatments after 3 months of therapy showed that patients with FM have a profile of resistance to first-line preventive drugs (Delussi et al, 2020 ). Tricyclic antidepressant amitriptyline was actually the most frequently prescribed drug for the treatment of migraine patients comorbid with FM (Delussi et al, 2020 ). However, researchers did not report the possible effect of amitriptyline on specific symptoms of FM and how the mild improvement of migraine could impact the disability linked to diffuse pain (Affaitati et al, 2020 ).…”
Section: Comorbidity With Other Pain Syndromesmentioning
confidence: 99%